A STUDY OF RELATIONSHIP BETWEEN C – REACTIVE PROTEIN AND MICROALBUMINURIA IN DIABETIC PATIENTS: C-Reactive Protein And Microalbuminuria in Diabetic Patients - Waheed, Palvasha; Naveed, Abdul Khaliq (Pakistan Armed Forces Medical Journal, 2016)
Objective: To see the relationship between C-reactive protein (CRP) and microalbuminuria in type 2 diabetic patients. Study Design: Cross sectional comparative study. Place and Duration of Study: Department of Biochemistry and Molecular Biology and Centre for Research in Experimental and Applied Medicine, Army Medical College Rawalpindi over a period of 2 years from January 2009 to December 2010. Material and Methods: Non-probability convenience sampling was done. A total of 80 (n=80) subjects were recruited in the study and were divided into four groups. Each group consisted of 20 patients. Group I consisted of normal healthy individuals, group II comprised normoalbuminuric type II diabetics, group III had microalbuminuric type II diabetics, and group IV consisted of overt albuminuric type II diabetic subjects. The albuminuria status was defined as (i) normoalbuminuria: albumin excretion rate (AER) less than 30 mg / 24h (ii) microalbuminuria: (AER) between 30-300 mg / 24h (iii) overt albuminuria: (AER) greater than 300 mg / 24h. Samples of 10 ml venous blood and 24 hour urine were collected. Plasma CRP was measured by turbidimetric method using Electa. Albuminuria was determined using Microlab semi-analyser (Randox, UK). Data were analysed using SPSS version 17 and Microsoft Excel worksheet 2010 with add on Statistical Package. Mean and standard error of mean (SEM) were used to describe numeric variables among different groups. Minimum and maximum values were also obtained to evaluate variations in the collected data. Analysis of variance (ANOVA) was applied to find out significant differences among groups. ANOVA was followed by Post Hoc Tuckey’s test for multiple comparisons among groups. A p-value of less than 0.05 was considered significant and a p-value of less than 0.01 was considered highly significant. Pearson’s correlation coefficient (r) was applied to find out the correlation of various parameters in different groups. A positive and negative value near 1 represented strong direct and inverse relationship respectively. Results: The mean ± SEM value of urinary albumin in group I was 27.91 ± 2.26 mg/day. In group II it was 27.37 ± 2.21 mg/day, in group III it was 220.52 ± 17.83 mg/day, in group IV it was 330.78 ± 26.75 mg/day. There was significant difference between all the groups (p<0.001). In group I, the mean ± SEM value of CRP was 1806.6 ± 183.32 ng/mL. In groups II, III and IV, the mean ± SEM value of CRP was 1987.26 ± 201.66 ng/mL, 2384.712 ± 241.99 ng/mL and 3338.60 ± 338.79 ng/mL respectively. There was significant difference between all the groups (p<0.001). Conclusion: The levels of CRP are higher in diabetics as compared to normal healthy controls and there is a progressive increase in the levels of CRP with increase in microalbuminuria in type 2 diabetics.